OCB-Altruism: Pengaruh Internal Locus of Control, Perceived Organizational Support dan Motivasi Intrinsik Sebagai Variabel Intervening - Habib Febriansyah; Paulus Wardoyo; Wyatti Saddewisasi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to determine factors that can improve OCB-Altruism at the Semarang Candisari Pratama Tax Service Office. The independent variable in this research is internal locus of control and perceived organizational support and the dependent variable is OCB-altruism with intrinsic motivation as mediating variables. This research uses quantitative methods using questionnaires to collect the required data. The sample in this study was 105 employees taken using the census sampling method. The analysis used was structural equation model (SEM) analysis using the SmartPLS analysis tool. The results of this research show that internal locus of control, perceived organizational support and intrinsic motivation have a significant positive effect on OCB-altruism. Internal locus of control and perceived organizational support have also been proven to influence intrinsic motivation. The intrinsic motivation variable functions to mediate the relationship between internal locus of control and perceived organizational support with OCB-altruism.